Estudo dos fatores associados à infecção chagásica em área endêmica do Rio Grande do Norte - Galvão, Camila Regalado (2009)
The Chagas disease is a infectious and parasite disease that has as the causative agent a Trypanosoma cruzi, a protozoan parasite that can be transmitted to humans by the faeces of triatomines ( barbeiros ) in the blood-sucking. To understand the relationship between factors associated with chagasic infection and the risk of transmission of Trypanosoma cruzi, this work aimed to make a correlation between the results of serology, obtained by different immunological techniques, used for diagnosis of Chagas disease and risk factors to which the population of the city of Apodi-RN is exposed, to be considered a endemic area. The case-control study was conducted with 199 individuals, which initially was applied a questionary about socio-economic questions and some risk factors which they were exposed and also favor the spread of disease. Then was given the diagnosis by immunological techniques of serology by indirect hemagglutination, ELISA and indirect immunofluorescence. From the diagnosis, the subjects were divided into case group (presence of infection) and control group (no infection). Regarding the descriptive characteristics of the sample, were found a higher frequency of female individuals (59.3%), between 36 and 50 years of age (36.7%), with low education level (91%) and income monthly up to 1 minimum wage (67.8%). The serology, performed by three techniques of different principles, had a reactivity of 38.9% by Indirect Hemagglutination, 39.7% by ELISA and 38.7% by Indirect Immunofluorescence. As the result of the serology, 71 of samples showed reactivity in 2 or more techniques. On some risk variables, was found a significant relationship between individuals who had been bitten by the triatomines and had positive serology for Chagas disease (93.3%). Other variables of risk revealed individuals who had positive serology and had domestic animal (80.3%), lived in poorly maintained homes (97.2%) and near the forest (84.5%). A better understanding of the dynamics of transmission of T. cruzi and the risk factors that contribute to its occurrence in a region are needed to develop effective strategies for control of Chagas disease in these áreas